2021
DOI: 10.1002/fes3.323
|View full text |Cite
|
Sign up to set email alerts
|

Higher relative humidity and more moderate temperatures increase the severity of rice false smut disease in the rice–crayfish coculture system

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The pooled analysis revealed that the disease severity was negatively correlated with maximum and minimum temperature with -0.96 and -0.87 respectively which indicated that the disease progression was significantly decreased by increasing both maximum and minimum temperature. Jiehui et al, (2021) also reported that the incidence of rice false smut was significantly correlated with average temperature at fortnight intervals after ear head emergence. This finding supported the approach of this study on designating the influence of temperature during the smut ball formation as it was the important indicator for increasing the disease severity in rice.…”
Section: Correlation Between Weather Parameters and Disease Severitymentioning
confidence: 90%
“…The pooled analysis revealed that the disease severity was negatively correlated with maximum and minimum temperature with -0.96 and -0.87 respectively which indicated that the disease progression was significantly decreased by increasing both maximum and minimum temperature. Jiehui et al, (2021) also reported that the incidence of rice false smut was significantly correlated with average temperature at fortnight intervals after ear head emergence. This finding supported the approach of this study on designating the influence of temperature during the smut ball formation as it was the important indicator for increasing the disease severity in rice.…”
Section: Correlation Between Weather Parameters and Disease Severitymentioning
confidence: 90%
“…A study was conducted to use the methodology with a slight modification of a low-temperature treatment (2 days at 20°C) to obtain highly infected spikelets (Hu et al, 2020). This considerably Previous studies demonstrated that inoculation was necessary during the booting stage and that infection establishment after the panicles headed was exceedingly challenging (Jiehui et al, 2022). This might be connected to the filament's structure and physiological status.…”
Section: Infection Processmentioning
confidence: 99%